O sistema de espaços livres na forma urbana de Patos de Minas - Amorim, Nayara Cristina Rosa (2015)
This research analyzes the configuration of the Open Spaces System in the urban form of Patos de Minas, one medium-sized city in the state of Minas Gerais. The open space is characterized like everyone open space of edification and is one of the main morphological elements, able to contribute to the conservation and enhancement of the landscape, organize the urban form and confer identity to the cities. The open space is a major characterizer of the different urban landscapes present in the city. Starting from the study of ecological setting, spatial, land ownership and typological of those spaces, sought the understanding that everyone, each one with its characteristics and functions, are interconnected in a systemic way, structuring the environmental function, social, cultural and landscape, present in the urban dynamic. This approach enables elaborate a systemic view of the urban structure, in which it is observed, not just the sets of open spaces, but also their interactions and articulations with the edified, with society, with the physical support and with the urban form.